Determination of quantum yields of semiconductor nanocrystals at the single emitter level via fluorescence correlation spectroscopy. Issue 15 (4th April 2018) - Abbandonato, Gerardo; Hoffmann, Katrin; Resch-Genger, Ute
Abstract : A microscopy-based method to determine fluorescence quantum yields Φ F of dispersed semiconductor nanocrystals at ultralow concentration with fluorescence correlation spectroscopy (FCS) is presented. Abstract : Comparing the photoluminescence (PL) properties of ensembles of nanocrystals like semiconductor quantum dots (QDs) with single particle studies is of increasing interest for many applications of these materials as reporters in bioimaging studies performed under very dilute conditions or even at the single particle level. Particularly relevant is here the PL quantum yield ( Φ F ), which determines the signal size together with the reporter's molar extinction coefficient and is a direct measure for nanocrystal quality, especially for the inorganic surface passivation shell and its tightness, which can be correlated also with nanocrystal stability and the possible release of heavy metal ions. Exemplarily for red and green emitting CdTe nanocrystals, we present a method for the determination of Φ F of nanoparticle dispersions at ultralow concentration compared to cuvette measurements using fluorescence correlation spectroscopy (FCS), a single molecule method, and compared to molecular dyes with closely matching spectral properties and known Φ F . Our results underline the potential of this approach, provided that material-inherent limitations like ligand- and QD-specific aggregation affecting particle diffusion and QD drawbacks such as their complex and power-dependent blinking behavior are properly considered as shown here.